Nomination Violence in Uganda's National Resistance Movement - Anne, Mette Kjaer; Mesharch, W. Katusiimeh (African Affairs, 2021)
Institutional explanations of intra-party violence rarely address political economy dynamics shaping the institutions in question, and therefore they fail to understand their emergence and their stability. Specifically, focusing on institutional factors alone does not enable a nuanced understanding of candidate nomination violence and why some constituencies are peaceful while others are violent. This article theorizes nomination violence in dominant-party systems in sub-Saharan Africa. Drawing on political settlement theory, it examines the nature of nomination violence in Uganda’s October 2015 National Resistance Movement (NRM) primaries. We argue that the violence is a constitutive part of Uganda’s political settlement under the NRM. Nomination procedures remain weak in order for the NRM ruling elite to include multiple factions that compete for access while being able to intervene in the election process when needed. This means, in turn, that violence tends to become particularly prominent in constituencies characterized by proxy wars, where competition between local candidates is reinforced by a conflict among central-level elites in the president’s inner circle. We call for the proxy war thesis to be tested in case studies of other dominant parties’ nomination processes.